A máscara da ópera em Dom Casmurro - Miyamoto, Margareth Ramos Teixeira (2006)
This study has the aim of investigating the opera's representation in D. Casmurro's speech, as an I mask, which unroll itself in three personas: Casmurro as an author, narrator and as a character, Bentinho. This expansion creates a correlation with the operistic tripartite structure, whose authorship is shared among the playwriter, the librettist and the musician, besides, it appears in the novel in chapters VIII - It's time , IX - The Opera and X Accepted the Theory , in which the narrator approches his life to an operistic spectacle. This operistic drama element in DC's structure, has been the target not only for the critics as we´ll see in chapter 2, but also for composers like João Gomes Jr., who had transformed DC in a theater show. The music score belongs to him, but the libretto was written by Antonio Picarollo, which could be found in the music section of Rio de janeiro's nacional library. To reach our goal and to be able of demonstrating the operistic scene built by the casmurro-author, we started with Machado de Assis' experience in the theater, trying to show to our reader how the author experienced his life that later he wrote in the novel. In chapter 2, we will recuperate the literary censorious' voice, because they analysed the opera that appears inside the novel, giving a special view of the methaphor and alegory that could be seen in DC. In chapter 3, the central focus will be the opera, its parts and relations with DC, showing how the overture, arias, intermezzos, preludes and leitmotifs are written in the narrative. Finally in chapter 4, our target will be to analyse the operistic mask inside the novel's speech through Casmurro's tripartite performance as long as a playwriter, librettist and musician